Rotating stall inception in axial compressors under periodic perturbations - Wanjing Dong; Yong Wang (2013 25th Chinese Control and Decision Conference (CCDC), 2013)
The inception to rotating stall in axial compressors with inlet distortions is theoretically investigated by studying the three state Moore-Greitzer model with periodic perturbations. The model is transformed into a normal form by using the center manifold theory. Based on the normal form, we derived analytically the periodic solutions as well as their stability boundaries. When the amplitudes of the perturbations are small, the theoretic results predict quantitatively well to those from numerical simulations of the full model.